THE EFFECT OF USING A THERMAL TERAHERTZ DEVICE PRIOR TO REHABILITATION EXERCISES ON REDUCING ELBOW JOINT PAIN AND IMPROVING RANGE OF MOTION IN ATHLETES WITH DISABILITIES - Atheer Fawaz karim (Proximus Journal Publishing, 2026)
Accordingly, the researcher conducted a case study by designing a rehabilitation program supported by modern modalities using a thermal terahertz device for athletes with disabilities suffering from elbow joint injuries. The significance of this research lies in establishing a rehabilitation protocol accompanied by a terahertz device for the injured limb, enabling the athlete to perform sport-specific activities related to this joint and to return rapidly to normal activity and achievement.
Keywords: thermal terahertz, range of motion, pain